2021
DOI: 10.3389/frobt.2021.707149
|View full text |Cite
|
Sign up to set email alerts
|

Task-Level Authoring for Remote Robot Teleoperation

Abstract: Remote teleoperation of robots can broaden the reach of domain specialists across a wide range of industries such as home maintenance, health care, light manufacturing, and construction. However, current direct control methods are impractical, and existing tools for programming robot remotely have focused on users with significant robotic experience. Extending robot remote programming to end users, i.e., users who are experts in a domain but novices in robotics, requires tools that balance the rich features ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As can be indicated from the quantitative and qualitative assessments of the current study, that the proposed HRI was able to combine the reactivity of the operator’s direct control with the powerful computer vision algorithms. It is worth noting that, similar studies like (Senft et al , 2021) which adopted semi-autonomous approach, demonstrated limited reactivity between the operator and the robot. As indicated in (Senft et al , 2021), the operator specifies a group of task-level steps without guiding the robot's motion throughout its path.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…As can be indicated from the quantitative and qualitative assessments of the current study, that the proposed HRI was able to combine the reactivity of the operator’s direct control with the powerful computer vision algorithms. It is worth noting that, similar studies like (Senft et al , 2021) which adopted semi-autonomous approach, demonstrated limited reactivity between the operator and the robot. As indicated in (Senft et al , 2021), the operator specifies a group of task-level steps without guiding the robot's motion throughout its path.…”
Section: Resultsmentioning
confidence: 86%
“…It is worth noting that, similar studies like (Senft et al , 2021) which adopted semi-autonomous approach, demonstrated limited reactivity between the operator and the robot. As indicated in (Senft et al , 2021), the operator specifies a group of task-level steps without guiding the robot's motion throughout its path. Operator’s guidance is essential in applications like radioactive isotopes production to avoid collision in crowded environment.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations